Assessment of the stated policies of prominent food companies related to obesity and non-communicable disease (NCD) prevention in Thailand - Nisachol Cetthakrikul; Sirinya Phulkerd; Nongnuch Jaichuen; Gary Sacks; Viroj Tangcharoensathien (BMC, 2019)
Abstract Objective To review the publicly available policies and commitments of selected food companies in Thailand relating to obesity and non-communicable diseases (NCDs) prevention, and to assess these stated policies and commitments against global recommendations. Methods Nineteen food and beverage companies, including 13 packaged food, three non-alcoholic beverage, two food retailer, and one fast food company were selected, based on their market share by sector and food category. A review of publicly available policies and commitments related to four domains (product reformulation, food marketing, nutrition information and food accessibility) was carried out for each company. Content analysis of all data was conducted, including a comparison of policy content against global recommendations in each domain. Results Eleven companies (58%) reported at least one policy or commitment across the four domains. The packaged food companies reported policies in all four domains while the beverage companies committed to implement policies in all except the accessibility domain. The food retailers and fast food company only had policies in the reformulation and nutrition information domains. Very few of the policies and commitments covered all of the recommended components in each domain, and most lacked sufficient specificity to allow detailed monitoring and evaluation. Conclusion A small number of the most prominent food companies in Thailand have several nutrition-related policies in place. However, these policies do not sufficiently cover recommended areas for NCD and obesity prevention. Moreover, the extent to which policy statements translate to implementation has yet to be evaluated. Successful implementation of nutrition-related policies by the food industry in Thailand will likely require concrete, measurable indicators to guide both corporate policy making as well as public monitoring. The Thailand Government requires greater capacity to establish effective multi-sector platforms for NCD prevention, and to evaluate food companies' policies and enforce compliance both with regulations and voluntary commitments.